Investigation of functionally graded lattice structure fabricated by 3D printing - Parthiban S/O Rajendran (Nanyang Technological University, 2023)
This study investigates the potential of functionally graded lattice structures (FGLs) fabricated by 3D printing. The primary objective is to evaluate the mechanical properties of both uniform lattice structures and FGLs using simulation software to analyse their elasticity and plasticity in response to loading conditions. A literature review of lattice structures and their potential applications are conducted, and computer-aided design (CAD) software is utilized to design and fabricate the lattice structures. Laser powder bed fusion (LPBF) is used to 3D print the optimal lattice structures, and compressive testing is carried out to evaluate their mechanical properties. Results show that FGLs exhibit superior mechanical properties compared to uniform lattice structures, with better elasticity and plasticity. The 3D printing process using LPBF is successful in fabricating the designed lattice structures, and compressive testing results show that the manufactured FGLs have higher strength and stiffness compared to the uniform lattice structures. Overall, this study contributes to the development of lattice structures that exhibit optimal mechanical properties for various engineering applications.